3D printing of nanocomposite pills through desktop vat photopolymerization (stereolithography) for drug delivery reasons - Sharma, Peeyush Kumar; Choudhury, Dinesh; Yadav, Vivek; Murty, U. S. N.; Banerjee, Subham (3D printing in medicine)
Background The desktop vat polymerization process or stereolithography printing is an ideal approach to develop multifunctional nanocomposites wherein a conventional solid dosage form is used as a reservoir for compliant administration of drug-loaded nanocarriers. Methods In this study, a nanocomposite drug delivery system, that is, hydrogel nanoparticles of an approved nutraceutical, berberine entrapped within vat photopolymerized monoliths, was developed for drug delivery applications. For the fabrication of the nanocomposite drug delivery systems/pills, a biocompatible vat photopolymerized resin was selected as an optimum matrix capable of efficiently delivering berberine from stereolithography mediated 3D printed nanocomposite pill. Results The obtained data reflected the efficient formation of berberine-loaded hydrogel nanoparticles with a mean particle diameter of 95.05 ± 4.50 nm but low loading. Stereolithography-assisted fabrication of monoliths was achieved with high fidelity (in agreement with computer-aided design), and photo-crosslinking was ascertained through Fourier-transform infrared spectroscopy. The hydrogel nanoparticles were entrapped within the pills during the stereolithography process, as evidenced by electron microscopy. The nanocomposite pills showed a higher swelling in an acidic environment and consequently faster berberine release of 50.39 ± 3.44% after 4 h. The overall results suggested maximal release within the gastrointestinal transit duration and excretion of the exhausted pills. Conclusions We intended to demonstrate the feasibility of making 3D printed nanocomposite pills achieved through the desktop vat polymerization process for drug delivery applications.